VIOLENCE AGAINST WOMEN: A GENDER-BASED ANALYSIS - Sri Widayanti (TheJournalish: Social and Government, 2023)
Violence against women is a widespread issue occurs in personal, cultural and structural level, both national and international. Defending women’s rights that have been corrupted since forever requires a strong commitment and hard work within all aspects of life from various elements of society. Among ways to eliminate violence against women is by analyzing policies, social programs, values and norms based on gender. Using this analysis, it is expected to figure out gender bias within policies, programs, norms and values implemented within society. The fact shows that many forms of violence against women occur due to women’s limited access in political, social, cultural, economic and religious life. This paper tries to elaborate a gender-based analysis as an alternative tool to defend women’s rights. Also, it is an effort to raise people’s awareness about gender issue and to struggle for a gender-based justice welfare society.